The Impact of Disclosing the Quality of the Internal Control System on Improving Institutional Performance: A Field Study on the Iraqi Banking Sector - Hasan Hadi Mousa (Global Academy of Business Studies, 2026)
Purpose: This study investigates the impact of disclosing the quality of the internal control system on improving institutional performance in the Iraqi banking sector, addressing the critical challenge of inadequate governance transparency amidst the Central Bank of Iraq's comprehensive reform program (2023–2025). Methodology: A descriptive-analytical and field-based approach was adopted. A structured questionnaire employing a five-point Likert scale was administered to a purposive sample of 285 respondents across Iraqi commercial, private, and Islamic banks, encompassing executive managers, financial managers, internal auditors, and audit committee members. Data were analyzed using descriptive statistics, Pearson correlation, multiple regression, and structural equation modeling via SPSS and AMOS. Results: The five COSO framework components—control environment, risk assessment, control activities, information and communication, and monitoring—collectively explained 61.8% of the variance in institutional performance (R² = 0.618, F = 89.4, p < 0.001). Control activities emerged as the strongest predictor (? = 0.311), while information and communication recorded the lowest disclosure level (mean = 3.48), reflecting digital transformation gaps. Conclusions: Transparent disclosure of internal control quality exerts a statistically significant positive influence on institutional performance. Private banks demonstrate higher disclosure levels in control activities and information systems, while government banks maintain comparative strength in the control environment component. Limitations: The study is constrained by its cross-sectional design, geographic focus on Iraq, and reliance on self-reported perceptions, which may not fully capture objectively verifiable disclosure practices across the entire banking sector. Contributions: This research provides empirical evidence from an emerging economy undergoing institutional reform, offering a context-specific framework for banking regulators and practitioners to enhance internal control disclosure and governance standards in alignment with international benchmarks.